SUDEP and epilepsy‐related mortality in pregnancy. Issue 7 (22nd April 2014) - Edey, Stephan; Moran, Nicholas; Nashef, Lina
Summary Although data are limited, research in 2004 estimated a 10‐fold increase in mortality in pregnancy in the United Kingdom in women with epilepsy (WWE) compared to women without epilepsy. We highlight epilepsy mortality in pregnancy based on the 2011 report of the United Kingdom Confidential Enquiries into Maternal Deaths, relating its findings to previous reports and epilepsy‐rates in pregnancy. Among 2, 291, 493 maternities (2006–2008), we estimated 0.6% or 13, 978 were in WWE. Fourteen deaths were epilepsy‐related, of which 11 (79%) were sudden and unexpected (SUDEP). Nine occurred during pregnancy and five were postpartum. Nine (64%) were in women taking lamotrigine, seven as monotherapy. We estimated that 1:1, 000 women died from epilepsy (mostly SUDEP) during or shortly after pregnancy. Epilepsy‐related mortality is a significant risk in pregnancy. Antiepileptic drug–related factors may be relevant. The high proportion of women taking lamotrigine may reflect United Kingdom prescribing practice. Recent observations from the European and International Registry of Antiepileptic Drugs and Pregnancy (EURAP), whereby women on lamotrigine, the levels of which significantly decrease in pregnancy, had more difficulties with epilepsy control, argue against this being the sole explanation. Given the potential risks, every attempt should be made to prevent seizures, particularly convulsive, during pregnancy and postpartum. This, we believe, includes being proactive in maintaining lamotrigine levels during pregnancy. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.